SAT0643-HPR Points To Consider for Health Professionals Undertaking Musculoskeletal Ultrasound for Rheumatic and Musculoskeletal Diseases: Progress of A Eular Task Force. (15th July 2016) - Siddle, H.J.; Mandl, P.; Aletaha, D.; Vliet Vlieland, T.P.; Backhaus, M.; Cornell, P.; D'Agostino, M.A.; Ellegaard, K.; Iagnocco, A.; Jakobson, B.; Jasinski, T.; Kildal, N.H.; et al.
Abstract : Background: Musculoskeletal ultrasound (MSUS) has evolved into an important method for identifying musculoskeletal abnormalities, confirming the diagnosis in patients with suspected inflammatory arthritis, monitoring therapeutic response, influencing clinical decision making and guiding interventions. The role of the non-medical health professional has advanced with many health professionals undertaking training and using MSUS to extend their scope of practice. Guidelines to support training for rheumatologists have been identified but currently there are not any recommendations to support the education and training needs of non-medical health professionals using MSUS. Objectives: The EULAR Task Force was established to reach a consensus on the role and education and training needs of non-medical health professionals undertaking MSUS for the management of patients with rheumatic and musculoskeletal diseases (RMDs). Methods: The EULAR Task Force comprised an expert group from 11 European countries. The Task Force met twice and included rheumatologists, nurses, physiotherapists, a radiologist, radiographer and podiatrist with patient representation. In the first meeting the aims of the Task Force were defined and fourteen research questions were developed. This was followed by a comprehensive systematic search of the literature to identify publications on the role of health professionals using MSUS, their competency requirements and training undertaken. During the second meeting the Task Force were presented with the results of the literature review which supported the formulation and consensus of "points to consider". The level of agreement between task force members for each "point to consider" was determined after the second meeting. Results: In total, seven "points to consider" were formulated. Two points covered the role and scope of health professionals using musculoskeletal ultrasound and one point addressed the application and feasibility in daily practice. Three "points to consider" focused on the training and competency required by health professionals and the final point addressed the added value in daily practice. The strength of the "points to consider" was D based on the category of evidence (3–4). A high level of agreement (range 9.0–9.7) was achieved between Task Force members. Additionally, the Task Force agreed upon eight topics for the future research agenda. Conclusions: Seven "points to consider" for health professionals using MSUS for the management of patients with RMDs were developed using a combination of research-based evidence and expert consensus approach. Disclosure of Interest: None declared